â€œFriends, Please do not choose to go to hellâ€: Linguistic Strategies and Discourse Functions of Appeals in Christian Religious Tracts - Akinwotu, Samuel Alaba; Ogundele, Toyin (NIU Journal of Humanities, 2021)
Even though the persuasive features of religious discourse have been widely studied, existing studies have not adequately examined the use of appeals to create and maintain interpersonal relation. This study accounts for the linguistic strategies and the discourse functions of appeal in 11 Christian religious tracts purposively selected from 40 tracts collected from about 15 churches/ministries in Ondo State, South-western Nigeria. The study which adopts Aristotleâ€™s theory of rhetoric identifies four major types of appeals namely; appeal to intimacy using direct address; appeal to introspection using question and answer; appeal to beliefs and actions using conditional clauses and; appeal to faith using declarative clauses. Writers of Christian religious tracts in the Nigeria rely on emotional appeals, logical proofs and ethics as means of maintaining interpersonal relation with their readers. Also, they assume the position of divine authority and/or of better informed persons to counsel their readers. Keywords: Appeal, Christian religious tracts, Rhetoric; Religious communication, Discourse functions.